Resilience Against Patriarchy in Nikita Gill’s Selected Poems - Sany Novela Sihite (Fakultas Ilmu Budaya, 2025)
This research was conducted by applying a qualitative method, emphasizing meaning in the form of written or spoken words from people. This research used in the form of poems that depict resilience against patriarchy by Nikita Gill as the data. I also used supporting information related to the poems that gathered from books, articles, online media, and several previous studies. There are two goals of the research, where the first goal is to know how resilience against patriarchy is presented in the selected poems and the second one is to find the significance of Nikita Gill’s selected poems.
Re Uploud File Repository 28 Januari 2026_Rudy K
Keywords: Resilience Against Patriarchy